Redescription of Neanoplius Banks (Hymenoptera: Pompilidae) - Pitts, James P.; Sadler, Emily A. (Zootaxa, 2019)
Neanoplius Banks, 1947 is a monotypic genus of Neotropical spider wasp. It has been ignored in taxonomic works since its description. We redescribe the genus and type species, provide illustrations, provide additional characters to help separate it from other closely related genera, and provide a discussion of probable evolutionary relationships of this interesting genus.